La enseñanza de gramática y de géneros académicos en carreras de ingeniería. Narrativa de una experiencia interdisciplinaria - Matiolli, Estela (Universidad Nacional del Litoral, 2021)
This work recovers the interdisciplinary experience coordinated by language teachers in the undergraduate courses of the Facultad de Ingeniería y Ciencias Hídricas de la Universidad Nacional del Litoral.  This action-research has been developing for more than a decade and aims to improve students' reading comprehension and writing, in a collaborative task between Language and specific subjects, which has allowed the implementation of didactic proposals in the different chairs. participants. It also seeks to reflect on the real feasibility of implementing the results derived from cooperative work and whether it is possible to think about these experiences independently of the current curricular structure based on divergent disciplinary paradigms. The task is part of the theoretical-methodological proposal of Functional Systemic Linguistics that studies the real discourses of each communicative context, in addition to considering contributions from the field of mathematics and chemistry didactics. The results so far show the productivity of incorporating transversal content on academic discourse in non-humanistic careers for the best academic performance of students and the need for not only teachers to be involved in these actions, but also the different instances of policy and Institutional management.